Signaling Pathways Involved in Megakaryocyte‐Mediated Proliferation of Osteoblast Lineage Cells. Issue 3 (March 2015) - Cheng, Ying‐Hua; Streicher, Drew A.; Waning, David L.; Chitteti, Brahmananda R.; Gerard‐O'Riley, Rita; Horowitz, Mark C.; Bidwell, Joseph P.; Pavalko, Fredrick M.; Srour, Edward F.; Mayo, Lindsey D.; Kacena, Melissa A.
<x xml:space="preserve">Abstract</x> Recent studies suggest that megakaryocytes (MKs) may play a significant role in skeletal homeostasis, as evident by the occurrence of osteosclerosis in multiple MK related diseases (Lennert et al., 1975; Thiele et al., 1999; Chagraoui et al., 2006). We previously reported a novel interaction whereby MKs enhanced proliferation of osteoblast lineage/osteoprogenitor cells (OBs) by a mechanism requiring direct cell–cell contact. However, the signal transduction pathways and the downstream effector molecules involved in this process have not been characterized. Here we show that MKs contact with OBs, via beta1 integrin, activate the p38/MAPKAPK2/p90RSK kinase cascade in the bone cells, which causes Mdm2 to neutralizes p53/Rb‐mediated check point and allows progression through the G1/S. Interestingly, activation of MAPK (ERK1/2) and AKT, collateral pathways that regulate the cell cycle, remained unchanged with MK stimulation of OBs. The MK‐to‐OB signaling ultimately results in significant increases in the expression of c‐fos and cyclin A, necessary for sustaining the OB proliferation. Overall, our findings show that OBs respond to the presence of MKs, in part, via an integrin‐mediated signaling mechanism, activating a novel response axis that de‐represses cell cycle activity. Understanding the mechanisms by which MKs enhance OB proliferation will facilitate the development of novel anabolic therapies to treat bone loss associated with osteoporosis and other bone‐related diseases. J. Cell. Physiol. 230: 578–586, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company